Effect of Environmental, Social, Governance (ESG) and Strategic Deviation on Firm Risk: Evidence from Manufacturing Sector in Emerging Market Asia - Exaudi Dualolo; Maria Ulpah (Syntax Literate, 2023)
The notion of sustainable development has gained widespread acceptance in the realm of social development. As a result, firms and their stakeholders are increasingly focusing on external elements such as environment, society, and governance (ESG). This study investigates the impact of ESG on firm risk measured by cash flow volatility. This study further examines whether strategic deviation moderates the relationship between ESG and firm risk. This research considers a sample of 139 manufacturing firms available in Refinitiv between 2018 and 2022 and applies the fixed-effect model. This study is a valuable contribution to the field of research on environmental, social, and governance (ESG) factors and their impact on strategic management. Specifically, it examines how ESG considerations and strategic deviation affect the level of risk faced by manufacturing firms. The result shows that ESG significantly reduces cash flow volatility but strategic deviation is insignificant in both affecting cash flow volatility and moderating the relationship of ESG and cash flow volatility. This study will serve as a valuable resource for managers in manufacturing organizations, providing them with insights into the importance of considering environmental, social, and governance (ESG) issues. The findings of this study highlight the impact of ESG and strategic considerations on cash flow volatility.